The Promise and Perils of Transnationalisation : NGO Activism and the Socialization of Women's Human Rights in Egypt and Iran. - Stachursky, Benjamin (Routledge advances in international relations and global politics., 2013)
Benjamin Stachursky's book questions the unvarying positive view of transnationalism on domestic forms of activism, arguing for a more nuanced analysis that permits an understanding of the enabling and restricting effects of transnationalism. Looking at the period from the mid-1980s up to present developments such as the Arab Spring, Stachursky analyzes the emergence and development of NGO activism in Egypt and Iran, the social, political, and legal context of NGO activism, and key domestic debates on the impact and legitimacy of the actors operating in women's rights activism.